REPUTATION AND WORD-OF-MOUTH PERCEPTION : CASE STUDIES IN INSTITUTIONAL MANAGEMENT - Christina Menuk Sri Handayani; Fauziyah Fauziyah; Tri Ariprabowo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this research is to analyze the perception differences of reputation and word of mouth between educational and non-educational program students in choosing UNIPA Surabaya as their place of study. Using quantitative approach with the survey method, we sample 172 educational program students and 164 non-educational program students. The data is processed using multiple regression by first going through validity, instrument reliability and classical assumption tests. Analysis showed that there are significant differences between educational and non-educational program students in choosing UNIPA Surabaya as their place of study seen from the word of mouth perception, but no significant differences seen from the reputation perspective.